Stock Market Reactions to Legislated Tax Changes: Evidence from the United States, Germany, and the United Kingdom - Bernd Hayo; Sascha Mierzwa (Philipps-University Marburg, School of Business and Economics, 2020)
We study the effect of tax policy on stock market returns in the United States, Germany, and the United Kingdom using GARCH models and a unique daily dataset of legislative tax changes during the period 1 December 1978 to 31 January 2018. We find that days of discretionary tax legislation during all stages of the process often matter for returns, both in terms of statistical significance as well as economic relevance. Further disaggregating the tax shocks shows that news about personal income tax cuts affects stock market returns positively, whereas business tax legislation is rarely influential. We find evidence of stock market spillovers, mainly from US tax changes to European stock markets, but, albeit less pronounced, also the other way round. In several cases, we measure significant effects of changes in tax legislation on the days the changes are implemented. The US House Committee Report appears to be the most influential legislative stage in our sample. During the financial crisis, stock markets were more responsive to tax legislation. Finally, S&P500 returns tend to react at earlier legislative stages than do DAX returns, whereas FT30 returns barely react on days of domestic legislative action.
Keywords: E62; F65; G18; H24; H25; 330; Fiscal policy; legislative tax changes; stock markets; income tax; business tax; indirect tax; Germany; United Kingdom; United States